Assessing Variability in Children’s Exposure to Contaminants in Food: A Longitudinal Non-Targeted Analysis Study in Miami, Florida - Luciana Teresa Dias Cappelini; Olutobi Daniel Ogunbiyi; Vinícius Guimarães Ferreira; Mymuna Monem; Carolina Cuchimaque Lugo; Monica Beatriz Perez; Piero Gardinali; Florence George; Daniel M. Bagner; Natalia Quinete (Journal of Xenobiotics)
Food is essential for human survival; however, food can be an important route of exposure to contaminants. This study investigated the presence and distribution of anthropogenic contaminants in food consumed by families with small children in South Florida, United States, evaluating seasonal and socio-economic variabilities in chemical composition. QuEChERS protocols, followed by non-targeted analysis (NTA) using an LC-Orbitrap HRMS system, were used for the comprehensive screening of organic contaminants. The compounds were annotated and identified with the Compound Discoverer (CD) software, and contaminant distributions were analyzed using boxplots and Principal Component Analysis (PCA). The results showed significant seasonal and socio-economic differences in contaminant distributions (p < 0.05). In the wet season, a predominance of polymers and surfactants, such as dodecanedioic acid and N-dodecylacrylamide, were found in food, which might be due to increased transport of industrial pollutants during increased precipitation, while plasticizers (e.g., bis(2-ethylhexyl) phthalate) and drugs (e.g., warfarin) were more prevalent during the dry season, which could be related to less dilution effects in this period. A higher abundance of 1-nitrosopiperidine, present in cured meats, was noted in food from upper socio-economic classes, while the lower class showed higher abundance of benzocaine, a common topical anesthetic.